Od projektu polonistycznego do proekologicznego w klasie integracyjnej SP (opis projektu) - Balcerek, Helena (Paidia i Literatura, 2022)
The main purpose of Helena Barbara Balcerek’s article is to present an original project aimed at the amplification of both the language potential (communication competences) and the literary-cultural potential of sixth-grade primary-school students. The project’s method consists in problem-based learning which integrates literary-cultural content-oriented teaching and language education (including rhetoric) with educational and prosocial processes. Reflections yielded by an in-depth analysis and interpretation of texts used in the project as well as discussions concerning the problem of human values and needs lead, as it turned out during the project’s execution, to ecological issues and climate challenges facing the contemporary world. A large group of students have come up with practical ideas as to the use of available resources as means to resolve the climate crisis and to undertake pro-ecological actions.